KERUGIAN NEGARA AKIBAT PENYALAHGUNAAN WEWENANG PIMPINAN BANK PADA PUTUSAN TINDAK PIDANA KORUPSI NOMOR PERKARA 10/PID.SUS-TPK/2022/PN SMG - Ratnasari Puspitarini; Elfrida Ratnawati (LPPM Universitas Ekasakti Padang, 2023)
In many cases of corruption, apart from the existence of bad conspiracy, the perpetrators were almost entirely related to the abuse of authority and position which was carried out very precentable by structured. The modus operandi of corruption in the banking itself occurs by way of abuse of authority over positions carried out by the Bank's leadership, so that it can have an impact on public distrust of the banking industry. In some cases,condition of customer confidences drop in the bank's performance will have an impact on the occurrence of a “rush money” where in these conditions customers withdraw money on a large scale, this can result to make the economic country collapps if it does not handled properly. Authors used a descriptive research method that tried to dissect the relationship between the abuse of authority in the leadership position of the Bank and state losses. From the research results obtained a finding the corruption can cause losses to state finances and economic shocking, including cases of corruption that occur due to misuse of bank leadership associated with their duties and authorities in a position.